RISK PERCEPTION AFFECTING TO WORKING BEHAVIOR OF AIRSIDE OPERATION OFFICER AT DON MUEANG INTERNATIONAL AIRPORT IN THE COVID-19 PANDEMIC - Suppharangsan, Tanida (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The purposes of this research are 1) To study the level of risk perception and the working behavior of the airside operations officer at Don Mueang International Airport in the COVID-19 pandemic situation. 2) To compare the working behavior of the airside operations officer at Don Mueang International Airport in the COVID-19 pandemic situation 3) To study risk perception affecting to working behavior of airside operation officer at Don Mueang International Airport in the COVID-19 pandemic situation. The sampling of this research were 86 employees who working in airside operation department at Don Mueang International Airport. The researcher uses a random sampling method based on the principle of stratified random sampling by drawing numbers for the list of airside operation officer who work Don Mueang International Airport. The survey for this research and uses questionnaires as tools for research data collection and using a computer software program for statistical analysis. The statistical methods used in data analysis are percentage, mean, standard deviation, t-Test, ANOVA, Pearson’s Product Moment Correlation Coefficient. The research hypothesis testing resulting are as follows: 1) The difference in demographic characteristics affecting to have different the working behavior of the airside operations officer at Don Mueang International Airport in The COVID-19 pandemic situation. The research hypothesis testing revealed that gender and status have differences affect the operational behavior of the airside operation officer at Don Mueang International Airport in the COVID-19 pandemic situation at statistically significant at the 0.05 level, but the different of age, education, work level, and the function in the airside operations department not have different working behavior of the airside operations officer at Don Mueang International Airport in the Covid-19 situation. 2) Overall of Working behavior of airside operating officers was found that the overall of risk perception of airside operation officer is related to the overall of working behavior of airside operation officers at Don Mueang International Airport in The COVID-19 pandemic situation.